Levi Kane’s Utterances: Speech Acts in The Gorge Movie (2025) - Khodijah, Fadila Umi; Norahmi, Maida; Farid, Rezqan Noor; Rahman, Erwan; Hayati, Sifa (Journal of English Language and Education, 2025)
This research investigates the use of speech acts by Levi Kane, the main character in the 2025 romantic action-thriller film The Gorge, through the framework of Searle’s Speech Act Theory. The study aims to classify and analyze Levi’s utterances based on their types, forms, and pragmatic levels to understand how language reflects his identity and emotional transformation. Employing a descriptive qualitative method, 170 utterances were analyzed from the film’s official transcript. The utterances were categorized into five speech act types (assertive, directive, commissive, expressive, and declarative), identified as either direct or indirect, and evaluated according to three pragmatic levels: locutionary, illocutionary, and perlocutionary. The findings reveal that assertive speech acts are the most dominant, followed by directives, expressives, and commissives. No declaratives were found, which reflects Levi’s role as an executor rather than a formal authority. Direct speech acts significantly outnumber indirect ones, illustrating his concise and action-oriented communication style. At the pragmatic level, illocutionary acts dominate, suggesting that Levi’s speech is highly intentional and performative. These results indicate that Levi’s speech patterns mirror his shift from a reserved soldier to an emotionally engaged individual. The study highlights how pragmatic analysis can be used to trace psychological depth and character development in film, providing valuable insights for linguists, educators, and scholars of media discourse